Molecular Mechanisms of Polyphenols in Management of Skin Aging - Dwevedi, Deepti; Srivastava, Ankur (Current Aging Science, 2024)
The natural process of skin aging is influenced by a variety of factors, including oxidative stress, inflammation, collagen degradation, and UV radiation exposure. The potential of polyphenols in controlling skin aging has been the subject of much investigation throughout the years. Due to their complex molecular pathways, polyphenols, a broad class of bioactive substances present in large quantities in plants, have emerged as attractive candidates for skin anti-aging therapies. This review aims to provide a comprehensive overview of the molecular mechanisms through which polyphenols exert their anti-aging effects on the skin. Various chemical mechanisms contribute to reducing skin aging signs and maintaining a vibrant appearance. These mechanisms include UV protection, moisturization, hydration, stimulation of collagen synthesis, antioxidant activity, and anti-inflammatory actions. These mechanisms work together to reduce signs of aging and keep the skin looking youthful. Polyphenols, with their antioxidant properties, are particularly noteworthy. They can neutralize free radicals, lessening oxidative stress that might otherwise cause collagen breakdown and DNA damage. The anti-inflammatory effects of polyphenols are explored, focusing on their ability to suppress pro-inflammatory cytokines and enzymes, thereby alleviating inflammation and its detrimental effects on the skin. Understanding these mechanisms can guide future research and development, leading to the development of innovative polyphenol-based strategies for maintaining healthy skin.
Keywords: Polyphenol